Factors Associated with the Incidence of Tuberculosis - Angraini, Wulan; Sinta, Klara; Febriawati, Henni; Kosvianti, Emi; Rizal, Achmad Faisal; Sarkawi, Sarkawi (Jurnal Kesehatan Prima, 2025)
Tuberculosis or also known as TB is an infectious disease caused by the bacterium Mycobacterium tuberculosis, in which the bacterium can not only attack the lungs but also attack other organs such as carbuncles, skin, meningitis, lymph nodes, intestines and other people. The transmission originates when the patient sneezes or coughs so that the germs spread through the air in the form of sputum. This study aims to determine the factors that influence the incidence of tuberculosis in the work area of the Bengkulu Pasar Ikan Market Health Center. This type of research is quantitative with a cross sectional approach. The research was conducted at the Fish Market Health Center in Bengkulu City from November 25 to December 24, 2022. The research sample was taken from a total of 64 people using a purposive sampling technique. Data analysis was carried out by univariate and bivariate analysis using the chi-square test with Î± = 0.05. The results of the study showed that there was an influence between age, knowledge, attitudes, gender, smoking habits, ventilation, occupancy density, humidity and lighting related to the incidence of tuberculosis.